Vitamin D, immune microenvironment, and cervical lesions: mechanisms and therapeutic strategies from polyps to carcinoma - He, Zheng; Du, Cheng (Frontiers in Nutrition, 2025)
Persistent infection with high-risk human papillomavirus (HPV) together with progressive dysregulation of the cervical tumor immune microenvironment (TIME) drives the continuum from cervical intraepithelial neoplasia (CIN) to invasive cancer. Vitamin D (VitD) signaling via the vitamin D receptor (VDR) intersects this trajectory by inducing antimicrobial peptides, strengthening epithelial barrier function, redirecting dendritic cells (DCs) toward less inflammatory programs, attenuating Th1 and Th17 activity, and promoting regulatory T-cell responses. These coordinated effects can shift a “cold” cervical niche toward improved viral clearance and controlled inflammation. Clinically, a randomized trial reported that biweekly cholecalciferol at 50,000 IU for 6 months increased CIN1 regression to 84.6%. Preclinical and early clinical studies also suggest that VitD enhances radiotherapy (RT) responses by suppressing autophagy, promoting apoptosis, and reducing the neutrophil-to-lymphocyte ratio (NLR). Translational options include systemic supplementation with monitoring of 25-hydroxyvitamin D (25 [OH]D), cervicovaginal delivery to concentrate drug at lesion sites, and development of low-calcemic VDR agonists used alongside standard antiviral and oncologic care. Key uncertainties remain, including tissue heterogeneity of VDR expression, optimal dosing windows and target 25(OH)D ranges for cervical endpoints, and safety at higher exposures such as hypercalcemia. This review aims to integrate mechanistic and clinical evidence, define stage-specific roles of the VitD–VDR axis across the CIN–cancer spectrum, and outline practical strategies and research priorities for VitD-based adjunctive interventions in HPV-associated cervical disease.